COVID-19 Budget Refocusing: Evidence from Indonesia - Wulan Rachmadani; Djoko Suhardjanto; Doddy Setiawan; Samsul Rosadi (Yayasan Ilomata, 2022)
This study aims to know the factors that influence regional government budget re-focusing in Indonesia because of COVID-19. This study uses regression analysis with the samples of 119 regional governments in Java. Java is one of the islands in Indonesia with the most significant population. It shows that the rate of patient recovery and economic impact influence the re-focusing regional Government in Indonesia. The implications of COVID-19 push the Indonesia government to re-focus re-budgeting. This study contributes to re-budgeting literature or regional government re-focusing in handling the COVID-19 impact in Indonesia